Hand microbial eczemas - O. B. Tamrazova; M. V. Novoseltsev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article concerns with the case dermatitis of hands. It analyses the modern classifications of hand dermatitis, epidemiological aspects, initiating agents, clinical treatment and therapeutical principals. The special focus is put on microbal eczemas and chronical allergodermathosis of hands. Among the pathogenetical factors of development and maintaining of dermatological inflammation the problem of microbacterial infection of skin is emphasized. The effectiveness and safety of external therapy of patients with microbal and chronical hand eczemas is proven and established while using the multicomponental medication Triderm.